Tafsir Tarbawi: The Verse Of Education As A Basis For The Concept Of Ethical Education Of Ibn Miskawaih And Al-Ghazali (Comparative Analysis) - rosyid, junaedi (Jurnal Edusci, 2024)
Tafsir Tarbawi is a subject at the Faculty of Tarbiyah and Faculty Teacher of Training that seeks to find educational concepts in interpreting educational verses in the Qur'an. This article rests on educational verses examining the history of the development of moral education, which found a crossroads between Ibn Miskawaih and al-Ghazali, where the tradition inherited by the first figure is commonly referred to as the rational tradition. In contrast, the second figure is referred to as the mystical tradition. To obtain clarity on the format of Ibn Miskawaih's thinking pattern, which some parties call a driver of progress and vice versa, al-Ghazali, whom some parties accuse as one of the causes of the stagnation of the dynamics of intellectual movement in the Muslim world, the author tries to dialogue the thoughts of moral education of the two figures. This study is carried out by analyzing the comparative thinking of the concept of moral education both in aspects: basic concepts, human existential structure, moral virtues, and components of moral education